4CPS-144 Establishment of a pharmaceutical standardised interview concerning biosimilars of infliximab in the daycare clinic of a gastroenterology department for patients affected by inflammatory bowel disease. (March 2019) - Coget, E; Laffont-Lozes, P; Velasco Gonzalvo, V; Huc, D; Pineton de Chambrun, G; Altwegg, R; Blanc, P; Pageaux, GP; Rosant, D; Breuker, C
Abstract : Background: Anti-TNF monoclonal antibodies such as infliximab effectively treat inflammatory bowel disease (IBD). Currently they are recommended after failure or contraindication of corticosteroid/immunosuppressive therapy. The use of infliximab's biosimilars is an important question due to health costs and with the objective of improving healthcare. Purpose: Our goals were to evaluate the knowledge about biosimilars of patients treated with the reference product (RP), assess the number of patients who would accept switching to a biosimilar and to produce an economic analysis. Material and methods: From May to September 2018 we conducted a prospective observational study in the daycare clinic of the Gastroenterology Department. A standardised pharmaceutical interview for patients affected by IBD treated with RP was carried out. An evaluation of the knowledge of biosimilars was performed, before a point of information. Thereafter, the patient's opinion on the possibility of taking biosimilars was collected and the reasons for refusal as well. The pharmaceutical interview was saved in the patient's record which the prescribers could consult. An analysis of the savings in case of a transition to a biosimilar was realised. Results: Sixty-four patients participated in our study (46 Crohn's disease, 18 ulcerative colitis) all treated by RP for over a year. Mean age was 44. Ninety-two per cent of patients (n=59) had never received any information about biosimilars. After the interview, 38% (n=24) of patients were favourable to switching to biosimilars, 39% (n=25) were indecisive, 23% (n=15) were unfavourable. The unfavourable patients were concerned about tolerance (15% n=6) or efficiency loss (18% n=7) or both (35% n=14). Others preferred to discuss it with their doctor (30% n=12). In total, six patients moved onto biosimilars, which represented an economy of €1, 855/year. It would have been €8125 if all favourable patients had changed and €21 750 if all participants had accepted. Conclusion: Very few patients knew about biosimilars but after the pharmaceutical interview many were in favour of switching. Few willing patients actually changed to biosimilars, but one of the explanations was the lack of information. Therefore, our study showed that delocalising a pharmacist in the daycare department permits the evaluation of the patient's knowledge concerning their treatment and to provide specific information. References and/or acknowledgements: http://www.worldgastroenterology.org/UserFiles/file/guidelines/inflammatory-bowel-disease-english-2015-update.pdf No conflict of interest.